THE USE OF BOARD GAME IN TEACHING SPEAKING TO YOUNG LEARNERS - Syakur, M. Arief (Universitas Nusantara PGRI Kediri, 2020)
The purpose of this study was to present a literature review of the advantages of using board game media in teaching speaking to young learners. The researcher examined seventeen articles and theses related to the use of media board games in teaching speaking. The results of the literature review were used to identify the advantages of using board game media in teaching speaking especially to young learners. The advantages of using board game in teaching speaking to young learners are as followed board game provides a fun learning, attracts the students’ attention to participate actively, and helps the students to enjoy communicating verbally. The results of this study were expected to be able to be used as an information and reference material for teachers or researchers for further research. In short, the use of board games in teaching speaking to young learners can be a new strategy that can be used by English teachers.